Strain smoothing for compressible and nearly-incompressible finite elasticity. (1st April 2017) - Lee, Chang-Kye; Angela Mihai, L.; Hale, Jack S.; Kerfriden, Pierre; Bordas, Stéphane P.A.
Highlights: Strain smoothing is introduced in the framework of nearly-incompressible finite elasticity. The method alleviates shear locking. The method is expressed in the primal displacement unknowns only. The method is robust when using severely distorted meshes. Bubble functions are introduced in the displacement space to ensure stability. Abstract: We present a robust and efficient form of the smoothed finite element method (S-FEM) to simulate hyperelastic bodies with compressible and nearly-incompressible neo-Hookean behaviour. The resulting method is stable, free from volumetric locking and robust on highly distorted meshes. To ensure inf-sup stability of our method we add a cubic bubble function to each element. The weak form for the smoothed hyperelastic problem is derived analogously to that of smoothed linear elastic problem. Smoothed strains and smoothed deformation gradients are evaluated on sub-domains selected by either edge information (edge-based S-FEM, ES-FEM) or nodal information (node-based S-FEM, NS-FEM). Numerical examples are shown that demonstrate the efficiency and reliability of the proposed approach in the nearly-incompressible limit and on highly distorted meshes. We conclude that, strain smoothing is at least as accurate and stable, as the MINI element, for an equivalent problem size.